Fiscal Determinants Of Stress In The Maluku Islands Region - Izaac Tonny Matitaputty (EKO-REGIONAL, 2024)
This study identifies and assesses the impact of transfers to regions, local-own source revenue (Pendapatan Asli Daerah, PAD), gross regional domestic product, population, and construction cost index (CCI) on fiscal stress in regencies / cities in Maluku Province in 2015-2022. The data was obtained from Statistics Indonesia and Directorate of Financial Balance of the Ministry of Finance, analyzed quantitatively using panel data regression analysis and a fixed effect model obtained through Hausman test. The results indicate that the transfers to regions and PAD have a negative and significant impact on the fiscal stress, in contrast to the CCI. They suggest that higher transfers to regions and PAD would decrease the fiscal stress, and the CCI was a determinant in the local expenditure to increase regional growth and community services. The stress caused by limited PAD might be alleviated by the availability of potential regional resources and readiness of human resources.